Mycorrhiza Abundance and Biological Activity of Soil Under Iron-Fertilized Apple Cultivar (Red Chief) Grafted on Different Rootstocks Grown on a Calcareous Soil - Coskan, A.; Erdal, I.; Askin, A.; Dogan, K.; Akpinar, C. (Asian Journal of Chemistry, 2010)
The aim of this study was to examine mycorrhizal spore abundance, its infection rate and biological activity of soil depending on different rootstock, Fe sources or Fe doses. A field experiment was carried out to determine the effects of rootstocks on mychorizal abundance and root infection as well as CO2 production and dehydrogenase activity of soil. Doses of 25, 50 and 75g tree-1 Fe-EDDHA or FeSO4 were applied to apple trees (Red Chief cv.) grafted on dwarf (M9 and M26) and semi-dwarf (MM106) rootstocks. At flowering stages soil and root samples were collected and analyzed for their dehidrogenase activity, CO2 production, microbial biomass-C or mycorrhizal abundance and infection rate. Results revealed that neither rootstock nor Fe applications effect on mycorrhiza number in rhizosphere soil. The higher value was observed in the soil M26 planted and 75 g da-1 Fe-EDDHA applied plot (15 spores per g of soil). Therefore, infection rate showed significant variations related to rootstocks and Fe applications. The most adapted rootstocks was MM106 which 37.1 % of the roots infected by mycorrhiza. Fe-EDDHA was more effective than FeSO4 whereas both of them increased infection rate compared to control. There was no statistical difference between rootstocks in CO2 production; however, Fe-EDDHA is stimulated CO2 formation. The highest CO2 formation (11.55 mg CO2 100 g soil-1) observed in 50 g of Fe-EDDHA applied MM106 plot whereas the lowest was in M26 plot where Fe application not realized. Dehydrogenase activity was not affected by Fe sources; however, increased Fe application increased dehydrogenase activity. Rootstock of MM106 is statistically more effective on dehydrogenase and highest dehydrogenase value was observed in 50 g of Fe-EDDHA applied MM106 plot as 328 μg TPF 10 g soil-1. The highest biomass-C value was observed in 50 g of Fe-EDDHA applied MM106 plot, whereas the lowest was observed in 50 g of FeSO4 applied M9 plot. In general, Fe-EDDHA application was promote biomass-C more than FeSO4. Comparing to rootstocks, the highest effective rootstock was MM106 and followed by M26 and M29, respectively.